Hydrothermal Synthesis and Enhanced Photocatalytic Activity of TiO\(_2\)-Fe@CNTs Nanocomposite for Methylene Blue Degradation under Visible Light Irradiation - Chi, Le Ha; Long, Pham Duy; Chuc, Nguyen Van; Hong, Le Van (Communications in Physics, 2015)
TiO2 is one of the most attractive metal oxides because of the excellent chemical and photocatalytic properties. However, a problem in the application of TiO2 is the large band gap energy of 3.2 eV, corresponding to its photocatalytic activity under UV-light irradiation of wavelengths <387 nm. In this work, TiO2 nanoparticles doped with iron were grown on the surface of functionalized carbon nanotubes (TiO2-Fe@CNTs) to expand the photoabsorbance of the nanocomposite materials in the visible light region and improve their photocatalytic activity. TiO2-Fe@CNTs nanocomposite materials were synthesized by hydrothermal route in Teflon-sealed autoclave at 180oC for 10h. The FE-SEM and X-Ray diffraction measurements were taken for morphology and structural analysis of TiO2 nanoparticles doped with Fe coating on CNTs. The effects of the iron and CNTs on the enhanced photocatalytic activity for methylene blue degradation under AM 1.5 illumination of 100 mW.cm−2 were investigated.